PENYUSUNAN RENCANA PELAKSANAAN PEMBELAJARAN (RPP) KURIKULUM 2013 MELALUI PENDAMPINGAN UNTUK MENINGKATKAN KOMPETENSI GURU UPT SMP NEGERI 42 KECAMATAN MEDAN DELI TAHUN PELAJARAN 2018/2019 - Jamal Husein Harahap (JGK (Jurnal Guru Kita), 2022)
Preparation of the 2013 Curriculum Learning Implementation Plan (RPP) through Assistance to Improve the Competence of Upt SMP Negeri 42 Medan Deli District Teachers for the 2018/2019 Academic Year. The purpose of this school action research (PTS) is to increase the level of understanding of teachers, especially at UPT SMP Negeri 42 Medan in preparing and developing the 2013 Curriculum Learning Implementation Plan (RPP) through mentoring. The method used in this research is descriptive method. This research is in the form of School Action Research (PTS). The subjects of this research were 12 UPT SMP Negeri 42 Medan teachers from various subjects. The data collection technique used is in the form of observation sheets, interviews, discussions, documentation studies. Based on the results of observations of the first cycle of improvement actions using the 2013 curriculum Learning Implementation Plan (RPP) assessment format, the value reached 39.6 which means it is in the sufficient category, and the results of observations using the teacher activity assessment format in the Learning Implementation Plan Preparation Process (RPP) during the Assistance in Compiling the 2013 Curriculum RPP the score reached 36, which means it is in the good category. 2) Through the 2013 Curriculum Learning Implementation Plan (RPP) assessment format in cycle II which achieved a score of 86.7 was in the very good category.